Graphite-Derived Graphene-Based Composites for Ballistic Body Armor: A Systematic Literature Review - Isya Rahma Hanifah; Timbul Siahaan; Edy Sulistyadi (PT FORMOSA CENDEKIA GLOBAL, 2026)
The increasing development of modern ballistic threats has encouraged the advancement of lightweight and high-performance body armor materials capable of providing effective protection without reducing user mobility. Graphene, a two-dimensional carbon nanomaterial derived from graphite, has attracted significant attention in defense applications because of its exceptional mechanical properties. This study aims to review graphite-derived graphene-based composites for ballistic body armor applications through relevant national and international journals. The reviewed studies were analyzed based on material characteristics, ballistic energy absorption mechanisms, hybrid composite systems, fabrication methods, and development challenges. The results indicate that graphene improves ballistic resistance through stress-wave propagation, crack deflection, and enhanced energy dissipation mechanisms. In addition, graphene-based hybrid composites demonstrate improved ballistic limit velocity and reduced backface deformation compared to conventional ballistic materials. However, challenges such as high production cost, agglomeration, brittleness, and scalability limitations still hinder large-scale implementation. Overall, graphite-derived graphene shows strong potential for future lightweight ballistic body armor applications.